Analytical investigations of ground modifications assisting the detection of buried object - Valagiannopoulos, Constantinos; Tsitsas, Nikolaos L.; Sihvola, Ari H. (Nazarbayev University School of Science and Technology, 2016)
A ground-penetrating radar (GPR) antenna excites a perfectly electric conducting inclusion buried inside the ground. The scattering problem is solved semi-analytically via integral equation techniques. The permittivity and thickness of a superstrate deposited atop the ground are determined such that the detectability of the inclusion is significantly increased. Results from numerical simulations are presented exhibiting the effectiveness of the approach. Emphasis is given on the effects that the shape of the buried inclusion has on the scattered field.
Keywords: radar imaging; buried object detection; ground penetrating radar; integral equations; numerical analysis; permittivity